Silkworm Silk Can Become a High‐Strength and Super‐Toughness Spider‐Silk‐Like Fiber: Multipathway Engineering Strategies and Applications - Mengqi Wang; Zhiming Du; Aixin Tong; Yu Zhang; Yuxin Luo; Zhicheng Shi; Sijie Qiao; Zhiyu Huang; Annan He; Xiachao Chen; Guizhen Ke; Qing Liu; et al. (Small Structures, 2025)
Silkworm silk is an important high‐grade textile raw material, due to the outstanding wearing comfort and excellent mechanical properties. The advantages of silkworm silk in terms of biocompatibility, biodegradability, nontoxicity, and noninflammatory properties are increasingly being recognized, showing significant potential in multidisciplinary applications. However, the strength and toughness of silkworm silk are far less than that of spider silk, which largely limits the application of silk fibers in high‐end fields. How to endow the silkworm silk with strength and toughness as spider silk has been a huge challenge. Herein, the mechanical properties of silkworm silk and spider silk are first compared and the structure–property relationship derived from the unique hierarchical structure is revealed. Then, the recent progress in fabricating high‐performance silkworm silk that is comparable to spider silk by using gene editing, feed modification, regeneration or recombination spinning, and silk post‐treatment is reviewed. Subsequently, applications of high‐performance silkworm silk with higher strength and toughness are discussed. Finally, possible challenges and future development directions for large‐scale production and application of high‐performance silkworm silk are highlighted, which is expected to promote material design innovative for next‐generation devices and facilitate the industrialization development level for high‐performance silkworm silk.